ROBO4 variants predispose individuals to bicuspid aortic valve and thoracic aortic aneurysm. (January 2019) - Gould, Russell; Aziz, Hamza; Woods, Courtney; Seman-Senderos, Manuel; Sparks, Elizabeth; Preuss, Christoph; Wünnemann, Florian; Bedja, Djahida; Moats, Cassandra; McClymont, Sarah; Rose, Rebecca; Sobreira, Nara; et al.
Abstract Bicuspid aortic valve (BAV) is a common congenital heart defect (population incidence, 1–2%)1–3 that frequently presents with ascending aortic aneurysm (AscAA)4 . BAV/AscAA shows autosomal dominant inheritance with incomplete penetrance and male predominance. Causative gene mutations (for example, NOTCH1, SMAD6 ) are known for ≤1% of nonsyndromic BAV cases with and without AscAA5–8, impeding mechanistic insight and development of therapeutic strategies. Here, we report the identification of variants inROBO4 (which encodes a factor known to contribute to endothelial performance) that segregate with disease in two families. Targeted sequencing ofROBO4 showed enrichment for rare variants in BAV/AscAA probands compared with controls. Targeted silencing ofROBO4 or mutant ROBO4 expression in endothelial cell lines results in impaired barrier function and a synthetic repertoire suggestive of endothelial-to-mesenchymal transition. This is consistent with BAV/AscAA-associated findings in patients and in animal models deficient for ROBO4. These data identify a novel endothelial etiology for this common human disease phenotype. Individuals with biscuspid aortic valve and ascending aortic aneurysm show enrichment of rare variants inROBO4 . Functional studies suggest thatROBO4 mutations disrupt endothelial cell performance and contribute to pathological remodeling of aortic tissues.